A microstructure tuning strategy on hollow carbon nanoshells for high-efficient oxygen reduction reaction in direct formate fuel cells. (22nd May 2023) - Peng, Qin; Lu, Qingyun; Fu, Qian; Zhang, Liang; Li, Jun; Zhu, Xun; Liao, Qiang
Abstract: The microstructure of carbon supports for electrocatalysts plays a crucial role in dispersing active sites, establishing oxygen/ion transport channels, and thus determining the oxygen reduction reaction (ORR) activity. A facile and simple microstructure tuning strategy is adopted to synthesize hollow carbon nanoshells (CNSs) with tuneable microstructure in this study. The CNSs with expected macroporous (300–966 nm) and mesoporous (2–5 nm) structures were achieved by adjusting heating ramp rates during pyrolysis. The CNS prepared at 1 °C min −1 (CNS-1) possesses a well-developed mesoporous/macroporous structure, which is conducive to dispersing iron phthalocyanine during the synthesis and establishing triple-phase interfaces in the catalyst layer during the ORR. Therefore, the electrocatalyst (Fe–N/CNS-1), derived from the CNSs-1, exhibits a 44 mV higher half-wave potential (0.879 V vs. RHE) in a rotating disk electrode and a 14% higher maximum power density (16.1 mW cm −2 ) in a membrane-less direct formate fuel cell than that of Pt/C. This study delivers a promising microstructure tuning strategy for carbon supports to construct high-efficient ORR electrocatalysts. Graphical abstract: A microstructure tuning strategy for the carbon supports of the high-performance ORR catalysts to effectively establish triple-phase interfaces. Image 1 Highlights: A sample pyrolysis method was proposed to synthesize the macroporous CNSs. The microstructure of the CNSs was tuned by adjusting the heating ramp rates. Na2 CO3 templates played a vital role in the tuning process during pyrolysis. The microstructure of CNS-1 was conducive to dispersing FePc and establishing TPIs. Fe–N/CNS-1 exhibited an E1/2 (0.879 V) in a RDE and a Pmax (16.1 mW cm −2 ) in a DFFC.